Meningkatkan Pengetahuan Siswa Melalui Coaching Clinic Teknik Dasar Renang Pada Siswa Mts Al-Falah Fi’lial Kabupaten Gorontalo - Lamusu, Zulkifli (Universitas Negeri Gorontalo, 2025)
Swimming is an essential life skill, especially for the younger generation, because it not only supports physical fitness but also plays an important role in self-rescue efforts in aquatic environments. However, until now there are still many students at the Al Falah Junior High School (MTs) who have not received access to adequate swimming training, both in terms of facilities and competent instructors. Therefore, this community service activity aims to provide basic swimming training to 55 MTs students located in Vila Desaku in order to improve motor skills, awareness of water safety, and foster interest in swimming from an early age. This community service activity aims to. The methods used include lectures, questions and answers, and demonstrations, which are designed to help students understand and practice basic swimming techniques systematically. The training material covers five important aspects, namely body position, leg movements, hand movements, breathing techniques, and movement coordination. The results of the evaluation using observation sheets showed that 90% of students experienced an increase in understanding of basic swimming techniques, and 78.76% mastered basic swimming techniques. This activity has a positive impact on motor skills, self-confidence, and students' awareness of the importance of water safety. Therefore, this program is expected to be a model that can be replicated in other educational institutions in order to cultivate water sports from an early age.